Timothy Findley, His Biographers, and The Piano Man’s Daughter - Sherrill Grace (Text Matters, 2018)
In this paper, Sherrill Grace, Findley’s biographer, will examine her biographical practices in the context of Findley’s own memoir, Inside Memory, and his interest in creating fictional auto/biographers and auto/biography in several of his major novels (notably The Wars, Famous Last Words, The Telling of Lies, and The Piano Man’s Daughter). His fictional auto/biographers often use the same categories of document that Findley himself used—journals, diaries, archives—and this reality produces some fascinating challenges for a Findley biographer, not least the difficulty of separating fact from fiction, or, as Mauberley says in Famous Last Words, truth from lies. Like many writers, Findley kept journals all his life, and they are a key source of information for his biographer; however, his way of recording information and his creation of fictional journals means that a biographer (like the readers of his fictional auto/biographers) must tread carefully. While not a theoretical study of auto/biography, in this paper Grace will offer insights into the traps that lie in waiting for a biographer, especially when dealing with a biographee who is as self-conscious an auto/biographer as Findley.